A simple universal property of Thom ring spectra. Issue 1 (31st October 2018) - Antolín‐Camarena, Omar; Barthel, Tobias
Abstract: We give a simple universal property of the multiplicative structure on the Thom spectrum of an n ‐fold loop map, obtained as a special case of a characterization of the algebra structure on the colimit of a lax O ‐monoidal functor. This allows us to relate Thom spectra to E n ‐algebras of a given characteristic in the sense of Szymik. As applications, we recover the Hopkins–Mahowald theorem realizing H F p and H Z as Thom spectra, and compute the topological Hochschild homology and the cotangent complex of various Thom spectra.